Malignant tumors of the external auditory canal: diagnosis, treatment, genetic landscape, biomarkers, and clinical outcome - Pinelopi Samara; Michael Athanasopoulos; Anastasios Goulioumis; Ioannis Athanasopoulos (Open Exploration Publishing Inc., 2023)
Malignant tumors of the external auditory canal (EAC) are rare neoplasms that appear in the head and neck area. A common feature of these malignancies is their rarity, as well as their delayed diagnosis due to the appearance of non-specific symptoms that mimic various benign otologic conditions. The reported histological types of cancer of the external ear are: squamous cell carcinoma, basal cell carcinoma, malignant melanoma, Merkel cell carcinoma, angiosarcoma, adnexal carcinoma (including ceruminous adenocarcinoma and adenoid cystic carcinoma), and lymphoma (Lancet Oncol. 2005;6:411-20. doi: 10.1016/S1470-2045(05)70208-4). Several therapeutic interventions have been proposed, primarily orientated towards the cure of the patient, placing the surgical excision of the lesions at the tip of the spear. Subsequently and depending on the clinical stage and the pathological characteristics of the tumor, radiation, chemotherapy, a combination thereof, or some form of palliative treatment for particularly advanced cases, may be recommended. The aim of all the above-mentioned approaches is the complete resection of the mass with negative surgical margins along with lymph node dissection, the elimination of any residual disease or metastasis, and the improvement of survival. The anatomical complexity of the region will always remain a demanding challenge. Nevertheless, advances in the fields of ear microsurgery, imaging, radiation, molecular biology, and genomics have led to remarkable outcomes compared to the past, with a view to the patient's quality of life. Large, well-organized, and prospective studies with the participation of multiple centers in contrast to existing retrospective studies with a limited number of patients will help to establish universally accepted guidelines. The exploration of the molecular and genetic background of these cancers in conjunction with the search for new biomarkers and target molecules seems promising for providing upgraded and more personalized treatment modalities for the future.